COVID-19 in northeast Brazil: first year of the pandemic and uncertainties to come - Kerr, Ligia Regina Franco Sansigolo (Rev Saude Publica, 2021)
OBJECTIVE: To analyze the epidemic of COVID-19 in northeastern Brazil, one of the regions most affected by the virus. METHODS: The official data for COVID-19, from March 2020 to March 2021 in the states of the Northeast Region (NE), were used. The analysis of capital cities and states for accumulated weekly cases and confirmed deaths was made using the JoinPoint Trend Analysis application. RESULTS: In one year, the Northeast region reported 22.9% of the cases and 21.5% of the deaths in the country due to COVID-19. At the beginning of the pandemic, all states showed a growing number of cases, first in the capitals and then in the interior. Following this wave, decreases are observed in all states and their capitals, but with many still reporting a large number of cases. In the middle of the 2nd semester of 2020 the number of cases begins to increase again simultaneously in states and their capitals—some at explosive speed—especially in late 2020 and early 2021. A similar pattern is observed in deaths, which exceed or approach the peak seen in the first wave. In the first wave, all capitals and northeastern states adopted intense isolation measures. Fortaleza, Recife and Teresina reached the highest isolation index of all capitals, close to 0.60. This index decreases, with a slight growth trend until the end of December. With the exception of Fortaleza and Salvador, the other capitals fell to less than 0.40. CONCLUSION: The Brazilian NE and the country are in increasingly complicated health, social and economic situations. It is necessary to speed up vaccinations and maintain non-pharmacological measures: face masks, social distancing measures and hygiene care, in addition to policies to protect workers who have lost their incomes and to subsidize small business owners.